2020
DOI: 10.3389/fonc.2019.01541
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Biogenic Selenium Nanoparticles for Prostate Cancer Therapy With Reduced Risk of Toxicity: An in vitro and in vivo Study

Abstract: Selenium deficiency is associated with many physiological disorders including the high risk of cancer. The rehabilitation of selenium with different selenium supplements, however, fails due to their low therapeutic index. Therefore, it is advantageous to have a less toxic form of selenium for supplementation with potentially high anticancer activity. Here we show Bacillus licheniformis derived biogenic selenium nanoparticles at a minimal concentration of 2 µg Se/ml induce necroptosis in LNCaP-FGC cells, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…As opposed to conventional chemogenic syntheses, biogenic approaches give rise to thermodynamically stable yet structurally diverse SeNS products in a safe and eco-friendly manner, avoiding the need of post-production treatments [2]. To date, biogenic SeNMs were investigated for their applications in (i) biomedicine, as antimicrobial [19][20][21][22][23][24][25][26][27], anticancer [27][28][29][30][31][32][33][34][35][36][37][38] and antioxidant [27,[39][40][41] agents, due to their high biocompatibility towards eukaryotic in vitro and in vivo systems [22,28,40,42], (ii) photocatalysis, and (iii) biosensing or pollutant adsorption [43][44][45][46], leaving still unveiled the potentiality of these NSs as a bioimaging tool. In particular, the PL properties of SeNPs produced by bacteria just recently began to be explored, as in the case of those recovered from the environmental isolate Stenotrophomonas maltophilia SeITE02 under metabolically controlled growth conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to conventional chemogenic syntheses, biogenic approaches give rise to thermodynamically stable yet structurally diverse SeNS products in a safe and eco-friendly manner, avoiding the need of post-production treatments [2]. To date, biogenic SeNMs were investigated for their applications in (i) biomedicine, as antimicrobial [19][20][21][22][23][24][25][26][27], anticancer [27][28][29][30][31][32][33][34][35][36][37][38] and antioxidant [27,[39][40][41] agents, due to their high biocompatibility towards eukaryotic in vitro and in vivo systems [22,28,40,42], (ii) photocatalysis, and (iii) biosensing or pollutant adsorption [43][44][45][46], leaving still unveiled the potentiality of these NSs as a bioimaging tool. In particular, the PL properties of SeNPs produced by bacteria just recently began to be explored, as in the case of those recovered from the environmental isolate Stenotrophomonas maltophilia SeITE02 under metabolically controlled growth conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional content of the diet and the relationship between the nutrients and PCa risk is still unclear [52]. Specifically, with respect to selenium, there are studies that find a link with the PCa, pointing out an anti-inflammatory effect of supplemental selenium as a possible causal pathway [53,54]. Similarly, the Nutritional Prevention of Cancer Trial, originally developed to study the effect of selenium on non-melanoma skin cancer, found a 63% reduction in PCa risk among men taking selenium supplements [55].…”
Section: Discussionmentioning
confidence: 99%
“…SW30, [ 89 ] Bacillus pumilus sp. BAB‐3706, [ 90 ] Pseudomonas putida KT2440, [ 85 ] Azospirillum brasilense , [ 91 ] Bacillus licheniformis , [ 35 ] Vibrio natriegens , [ 92 ] Rhodococcus aetherivorans , [ 80 ] Pseudomonas alcaliphila , [ 93 ] Alcaligenes faecalis , [ 94 ] Pseudomonas stutzeri [ 95 ] and, more recently, Bacillus amyloliquefaciens SRB04, which has been shown to produce SeNPs smaller than 50 nm. [ 75 ]…”
Section: Preparation and Characterization Methods Of Se Nanoparticles (Senps)mentioning
confidence: 99%